Atomic layer deposition-assisted growth of CuAl LDH on carbon fiber as a peroxidase mimic for colorimetric determination of H2O2 and glucose. (25th March 2019) - Wu, Lihong; Wan, Gengping; Shi, Shaohua; He, Zhengyi; Xu, Xuefei; Tang, Yulin; Hao, Chuncheng; Wang, Guizhen
Abstract : An atomic-layer-deposited Al2 O3 -induced LDH growth strategy was proposed to prepare carbon fiber-supported ultrathin CuAl LDH nanosheets (CF@CuAl-LDH). The CF@CuAl-LDH exhibited superior peroxidase-like catalytic activity. Abstract : In this work, an atomic-layer-deposited Al2 O3 -induced LDH growth strategy was proposed to easily prepare carbon fiber-supported ultrathin CuAl LDH nanosheets (CF@CuAl-LDH). The uniform Al2 O3 coating on carbon fiber (CF) was obtained using an atomic layer deposition (ALD) method and was used as a pinpoint inductive layer to transform into ultrathin CuAl LDH nanosheets through hydrothermal treatment. The LDH nanosheets grew densely attached to the CF surface and the nanosheet thickness was only about 3.3 nm. The obtained CF@CuAl-LDH exhibited superior enzyme mimic activity because its unique structural features offered a large ion-accessible surface, an increased active site area, and efficient electron-transfer pathways. Accordingly, a simple and sensitive biosensor was developed for colorimetric determination of H2 O2 and glucose. The established method was successfully used to detect glucose in juice samples with satisfactory results.